بروتوكول التحديد التجريبي لمركز ثقل السفن وأهميته في عالم اتزان السفن - حوا, رامي; بربهان, ميشيل (Latakia University Journal -Engineering Sciences Series, 2019)
إن كارثة غرق العبارة المصرية السلام 98 التي فقدت اتزانها بسرعة وغرقت بهذا الشكل المأساوي الكبير, دعا المهتمين بالسلامة البحرية إلى تحليل هذه الحادثة وعزا بعضهم ذلك إلى الطوابق التي تم إضافتها إلى البنية الإنشائية الرئيسية للسفينة بدون الحساب الدقيق لمركز التوازن. يعتبر التحديد الدقيق لموضع ومركز ثقل السفينة ضرورياً لتحديد ارتفاع الميتاسنتر ولإنشاء منحني أذرع عزوم الاستعدال بصورةٍ صحيحة, حيث إن هذا التحديد قد يؤدي إلى تفادي نتائج كارثية يمكن أن تحدث عند جراء التحديد الخاطئ أو غير الدقيق لمركز الثقل. إن تحديد موقع مركز الثقل لسفينة فارغة ولكن بوجود جميع التجهيزات الأساسية باستخدام الطرق الحسابية يعتبر من القضايا المعقدة. لذا فإن أفضل طريقة للحساب بعد الانتهاء من تجميع التجهيزات الأساسية هي الطريقة التجريبية التي تدعى تجربة الميل. هذا البحث يتطرق إلى صياغة ترتيب هذه الطريقة بتفاصيله الدقيقة وفقا لبروتوكول غير موجود في أي من المراجع الهندسية البحرية حيث تعتبر هذه الدراسات سرية وخاصة بمراكز الأبحاث و ترسانات بناء السفن لما لها من قيمة علمية و مردود مادي. The catastrophic capsizing of Egyptian M/V ALSALAM 98 when it lost its stability pushed the marine experts to analyze this catastrophe. Some of them thought that one of the major causes was the bad measurements of new centre of gravity after a new structure was added to the accommodation of the vessel. Accurate spotting for vessel centre of gravity is necessary for the determination of Metacentre high and establish correct curve for moment arms. This prevents catastrophic results that can happen when the centre of gravity is incorrectly established. It is a complex duty to establish the centre of gravity for empty vessel employing calculation methods. Therefore, the final position for empty vessel centre of gravity is established following experimental method called (rake experiment). This study discusses the aspect of arranging these methods with all their details according to a Protocol which is not available in any marine engineering references. This study is classified as a confidential specific to centre of research and shipyards due to its high scientific value, besides having found materialistic output.